2008
DOI: 10.1186/1471-2180-8-111
|View full text |Cite
|
Sign up to set email alerts
|

Lethal photosensitization of wound-associated microbes using indocyanine green and near-infrared light

Abstract: Background: The increase in resistance to antibiotics among disease-causing bacteria necessitates the development of alternative antimicrobial approaches such as the use of light-activated antimicrobial agents (LAAAs). Light of an appropriate wavelength activates the LAAA to produce cytotoxic species which can then cause bacterial cell death via loss of membrane integrity, lipid peroxidation, the inactivation of essential enzymes, and/or exertion of mutagenic effects due to DNA modification. In this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 57 publications
0
59
0
1
Order By: Relevance
“…Additionally, light sources should be inexpensive, lightweight and highly flexible (Konopka & Goslinski, 2007). Despite the fact that the antimicrobial activity of LED light sources has been intensively investigated in various studies (Omar et al, 2008;Omar, 2010), the efficacy of visible light in combination with water-filtered infrared-A (VIS+wIRA) in killing bacteria has not previously been examined. This combination delivers a broad-band light source which could be used in combination with different photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, light sources should be inexpensive, lightweight and highly flexible (Konopka & Goslinski, 2007). Despite the fact that the antimicrobial activity of LED light sources has been intensively investigated in various studies (Omar et al, 2008;Omar, 2010), the efficacy of visible light in combination with water-filtered infrared-A (VIS+wIRA) in killing bacteria has not previously been examined. This combination delivers a broad-band light source which could be used in combination with different photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans was the most common species isolated from oral lesions/swabs of HIV positive patients accounting for 50% (2) of total 4 oral swabs. In previous studies done by Dunic et al, (2004), Mrudula Patel et al, (2006), Omar et al, (2008) C. albicans was the most common species isolated in oral swabs of HIV positive patients in the percentage of 77.7%, 83.5%, 78.6% and 84.5% respectively. Percentage of NAC spp.…”
Section: Image3 Candida Albicans (Apple Green) Candida Dubliniensis mentioning
confidence: 81%
“…removing the biofilm shield with a SW laser gave way to the next step which is killing the biofilm 4 . It was already shown that low level diode laser can take an active role in photodynamic therapy with as high as 99.9% killing rate possible after enhancing with a photosensitizer as shown by Wilson 5 . Thus laser-generated shockwave exposed the bacteria to a floating state, thus enabling a second strike.…”
Section: Laser Disruption and Killing Of Mrsa Biofilmsmentioning
confidence: 97%